Interaction of PsMYB4 with PsEGL3 inhibits anthocyanin biosynthesis in tree peony yellow flowers - Xiaoning Luo; Sijie Huang; Fangjun Jiang; Qianqian Shi; Yafeng Wen; Mengchen Li; Minhuan Zhang; Yanlong Zhang (Frontiers in Plant Science)
Tree peony is a traditional woody flower originating from China and possesses high ornamental value. The yellow cultivar is even more precious, known as the highest grade. However, the molecular mechanism underlying tree peony yellow flower formation is still unclear. Our present work identified two transcription factors (TFs), PsMYB4 and PsEGL3, which were highly expressed in yellow tree peony cultivar. Phylogenetic analysis indicates that PsMYB4 belonged to the R2R3-MYB repressor, while PsEGL3 was clustered into subgroup IIIf of bHLH family. Overexpression of PsMYB4 and PsEGL3 respectively in tobacco inhibited anthocyanin synthesis, with PsMYB4 overexpressing lines being more pronounced and the expression levels of structural genes NtC4H, NtCHS, NtCHI, and NtDFR were significantly downregulated, while the expression levels of structural genes in PsEGL3 transgenic lines showed no significant pattern. On the contrary, the expression of PsCHS, PsCHI, PsF3H and PsDFR increased in either PsMYB4 or PsEGL3 silencing tree peony petals, in which endogenous PsMYB4 and PsEGL3 genes were also inhibited to a certain extent. Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays further confirmed PsMYB4 could interact with PsEGL3. Moreover, in dual-luciferase (LUC) assay, PsMYB4 and PsEGL3 synergistically suppressed the promoter activity of PsCHS, PsCHI, and PsDFR, thus inhibiting anthocyanin biosynthesis branch and leading to a metabolic flow towards the flavonol synthesis branch. These findings provide a new perspective for revealing the molecular mechanism of the yellow flower formation in tree peony.